ANTI-COVID HADITH: MAQĀṢIDĪ ANALYSIS ON THE PROPHET’S GUARANTEE ON MEDINA’S STERILITY FROM ṬĀ‘ŪN - Akbar, Akbar; Ahmad, Arifuddin; Alwi, Zulfahmi; S. Puyu, Darsul (Faculty of Adab and Humanities - Alauddin State Islamic University of Makassar, 2021)
The insignificance of modern reality to the Prophet Muhammad [pbuh]’s statements and policies determines hadith misperception. This research examines the Prophet Muhammad [pbuh]’s assurance that Madinah was sterile from the ṭā‘ūn as a pandemic, even though Madinah was also infected with Covid-19. This study used a qualitative design utilizing library data based on al-Kutub al-Tis‘ah. The takhrij al-ḥadīṡ technique was used to track down the data that analyzed using an integrative technique developed by Ma‘ānī al-Ḥadīṡ and Maqāṣid al-Syarī‘ah. The findings revealed that the Prophet’s declaration about Madinah’s sterility due to the disease was part of his strategy for preserving the socio-political stability of Muslims who were pioneering a new civilization. Ḥifẓ al-daulah is a notion in Maqāṣid al-Syarī‘ah, it must be taken into consideration when attempting to determine the maqāṣid of each message and the Prophet. It can dispel the perception that the Prophet Muhammad’s hadith is irrelevant to the reality of modern life.ملخصإن عدم أهمية الواقع الحديث لأقوال الرسول صلى الله عليه وسلم وسياساته يحفز على سوء فهم الحديث. يفحص هذا البحث تأكيد النبي أن المدينة المنورة كانت عقيمة منذ ظهورها على أنها جائحة، على الرغم من إصابة المدينة المنورة أيضًا بـ Covid-19. استخدمت هذه الدراسة تصميمًا نوعيًا باستخدام بيانات المكتبة بناءً على الكتب التسعة. تستخدم تقنية تخريج الحديث لتعقب البيانات ثم تحليلها بتكاملية طورها علم معاني الحديث ومقاصد الشريعة. وكشفت النتائج أن إعلان الرسول صلى الله عليه وسلم عن عقم المدينة المنورة بسبب المرض هو جزء من استراتيجيته للحفاظ على الاستقرار الاجتماعي والسياسي للمسلمين الذين يقودون حضارة جديدة. حفظ الدولة كمقاصد الشريعة الذي يجب أن يؤخذ في الاعتبار عند محاولة تحديد مقاصد كل رسالة النبي. يمكن أن تبدد الفكرة القائلة بأن أحاديث النبي لا علاقة له بواقع الحياة الحديثة.